The Juggler's Guide to Managing Multiple Projects - Dobson, Michael (Project Management Institute, 2003)
Dobson says that you must first have a strong foundation in time management and priority setting, then introduces the concept of Portfolio Management to timeline multiple projects, determine their resource requirements, and handle emergencies, putting you in charge for possibly the first time in your life! The Juggler's Guide to Managing Multiple Projects does not forget the paperwork. Dobson supplies examples of business-tested forms, charts, logs, tables, and worksheets-everything project managers need to crash, level, analyze, plan, and control tasks. Forms were never better explained or illustrated. To ensure creative success, Dobson adds tips, shortcuts, and tricks of the project management trade with each example.